PENCEGAHAN BULLYING DAN CYBERBULLYING MELALUI PEMAHAMAN UNDANG-UNDANG PERLINDUNGAN ANAK DAN ITE DI SMKN 7 KOTA SERANG - Yolanda; Naila Nursyavika; Dinda Cahyanih; Maulina Fadhilah; Hilda Nurlisa (PT. Hasba Edukasi Mandiri, 2026)
The phenomenon of bullying and cyberbullying among students is increasing along with changes in social interaction patterns, both directly and in the digital space. This behavior not only impacts the psychological and social conditions of victims but also has the potential to cause legal consequences for perpetrators. One of the main factors causing this behavior is the low level of students' legal understanding, especially regarding the Child Protection Law and the Information and Electronic Transactions Law (ITE). This community service research aims to analyze the effectiveness of legal socialization in improving students' understanding of preventing bullying and cyberbullying. Using a participatory-educative approach through interactive lectures, group discussions, case studies, and pre-test and post-test evaluations, this study found that the socialization activity succeeded in significantly increasing students' understanding. The average pre-test score increased from 57.5 to 88.25 in the post-test, representing an improvement of 30.75 points (53.5%). The highest increase occurred in the understanding of articles in the Child Protection Law and the ITE Law. Thus, early legal education in the school environment has a strategic role in preventing bullying and cyberbullying and strengthening individual and family resilience.